Guideline for management of septic arthritis in native joints (SANJO) - Ravn Christen; Neyt Jeroen; Benito Natividad; Abreu Miguel Araújo; Achermann Yvonne; Bozhkova Svetlana; Coorevits Liselotte; Ferrari Matteo Carlo; Gammelsrud Karianne Wiger; Gerlach Ulf-Joachim; Giannitsioti Efthymia; Gottliebsen Martin; et al. (Copernicus Publications, 2025)
This clinical guideline is intended for use by orthopedic surgeons and physicians who care for patients with possible or documented septic arthritis of a native joint (SANJO). It includes evidence and opinion-based recommendations for the diagnosis and management of patients with SANJO. © 2023 Christen Ravn et al.